Do Works Councils Inhibit Investment? - Joachim Wagner; Claus Schnabel; Thorsten Schank; John T. Addison (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2005)
Theory suggests that firms confront a hold-up problem in dealing with workplace unionism: unions will appropriate a portion of the quasi rents stemming from long-lived capital. As a result, firms may be expected to limit their exposure to rent seeking by reducing investments, among other things. Although there is some empirical support for this prediction in firm-level studies for the United States, we investigate whether this is also the case in the different institutional context of Germany where the works council is the analogue of workplace unionism. Using parametric and nonparametric methods and establishment panel data, we find no evidence that the formation (dissolution) of a works council has an unfavorable (favorable) impact on investment. – – Theoretische Überlegungen deuten darauf hin, dass Firmen durch Arbeitnehmervertretungen auf Betriebsebene wie Gewerkschaften mit einem ?hold-up?-Problem konfrontiert werden, da letztere sich einen Teil der Quasi-Renten aus langlebigen Kapitalinvestitionen aneignen können. Deshalb mögen die Firmen ihre Anfälligkeit für derartiges ?rent seeking? dadurch verringern, dass sie ihre Investitionen zurückfahren. Während es für diese Hypothese empirische Bestätigungen durch Firmenstudien aus den USA gibt, untersuchen wir, ob dies auch in dem unterschiedlichen institutionellen Umfeld in Deutschland der Fall ist, wo statt Betriebsgewerkschaften Betriebsräte eine ähnliche Rolle spielen können. Unter Verwendung von parametrischen und nichtparametrischen Methoden sowie von Betriebspaneldaten finden wir keine empirischen Hinweise darauf, dass die Errichtung (bzw. Abschaffung) eines Betriebsrates einen negativen (bzw. positiven) Einfluss auf das betriebliche Investitionsverhalten hat.
Keywords: E22; J50; 330; Investment; works councils; rent seeking; Germany; panel data; Betriebliche Investitionspolitik; Betriebsrat; Rent Seeking; Schätzung; Deutschland; hold up-Problems